Striving for the brighter future: An experience of high school students as earthquake victims - Rose Mini Agoes Salim; Kusumasari Kartika Hima Darmayanti (International Journal of Evaluation and Research in Education (IJERE), 2020)
High school students’ experienced negative emotions caused by the earthquake that strucked Sigi District, Central Sulawesi, Indonesia. In addition to overcoming negative emotions, they were faced with deciding on a career decision. For this reason, this research aimed to determine the effect of Future Time Perspective (FTP) on Career Decision Self-Efficacy (CDSE) of 141 students from six high schools. Simple regression indicated that FTP positively affected the CDSE of high school students. Moreover, using multivariate regression analysis on FTP and five dimensions of CDSE, we found that FTP contributes positively and significantly to the five dimensions of CDSE. Therefore, the research implied that FTP based intervention program is able to promote CDSE.